Pulmonary sequelae of SARS-CoV-2 infection: a narrative review of long-term functional, radiological, and clinical outcomes in COVID-19 survivors, with a regional focus on Saudi Arabia - Fatimah Ali Zarbatan; Khaled Alawam; Ali Hakamy (Frontiers in Physiology, 2026)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has left an enduring legacy of pulmonary morbidity among millions of survivors worldwide. While the acute phase of COVID-19 has been extensively characterized, the long-term pulmonary sequelae collectively termed post-acute sequelae of SARS-CoV-2 infection (PASC) or long COVID remain incompletely understood, particularly across diverse geographic and demographic populations. This narrative review synthesizes current evidence on the long-term pulmonary consequences of SARS-CoV-2 infection, with emphasis on functional, radiological, and clinical outcomes in survivors. Literature was identified through systematic searches of PubMed, Scopus, and Google Scholar covering publications from January 2020 to September 2025, using pre-specified search terms related to long COVID pulmonary outcome; studies involving adult survivors with objectively assessed pulmonary outcomes were prioritized. This review addresses the pathophysiological mechanisms underlying pulmonary injury, the definition and clinical spectrum of long COVID, the trajectory of pulmonary function test (PFT) abnormalities—particularly reductions in diffusing capacity for carbon monoxide (DLCO) and radiological findings detected on high-resolution computed tomography (HRCT). Risk factors for persistent pulmonary dysfunction, the impact on health-related quality of life (HRQoL) and functional capacity, emerging evidence supporting structured pulmonary rehabilitation, and the specific context of Saudi Arabia and the Jizan region are also examined. A particular focus on the Arabian Peninsula is warranted given that regional populations carry a high burden of metabolic comorbidities including obesity, diabetes mellitus, and hypertension that may amplify pulmonary vulnerability to SARS-CoV-2 yet remain substantially underrepresented in the current literature. The available evidence suggests that impaired gas exchange most consistently reflected by reduced DLCO may represent the most prevalent long-term pulmonary consequence of COVID-19, with restrictive ventilatory patterns predominating over obstructive defects. Significant gaps persist regarding the long-term trajectory of these abnormalities, population-specific risk stratification, and the efficacy of targeted rehabilitation. Structured, longitudinal, multicenter research incorporating standardized PFT protocols is urgently needed to address these unresolved questions and guide evidence-based post-COVID pulmonary care.